Enhanced hydrogel loading of quercetin-loaded hollow mesoporous cerium dioxide nanoparticles for skin flap survival - Xiangjun Liu; Yikun Ju; Pu Yang; Naisi Shen; Yunyuan Shao; Anqi Yang; Rui Wu; Lanjie Lei; Bairong Fang (Materials Today Bio)
Flap techniques are indispensable in modern surgery because of their role in repairing tissue defects and restoring function. Ischemia-reperfusion and oxidative stress-induced injuries are the main causes of flap failure. Oxidative stress exacerbates cell damage through the accumulation of reactive oxygen species (ROS), thereby affecting flap function and survival. Effective management of these factors is essential for improving flap survival and post-operative recovery. In this study, we utilized hollow mesoporous cerium dioxide nanoparticles loaded with quercetin, which were later loaded into a light-cured double cross-linked hydrogel (HQu@BC) and injected into the flap site to activate macrophage reprogramming to maintain local ROS homeostasis and reduce inflammation. Quercetin scavenges ROS and reduces mitochondrial oxidative stress due to its intrinsic reducing structures such as catechols, carbon-carbon double bonds, and hydroxyl synergistic mesoporous cerium dioxide nanoparticles, and inhibits inflammation by suppressing M1 macrophage polarization. This system continuously regulates ROS levels, kills bacteria and ultimately reduces inflammation, thereby creating a favorable microenvironment for flap survival. This innovative injectable composite nanoparticle hydrogel material has anti-inflammatory, antioxidant, antimicrobial, and healing-promoting properties, providing a new approach to improving the success of flap surgery.